EDUKASI PASAR MODAL KOLABORATIF: STRATEGI PENINGKATAN LITERASI KEUANGAN DAN MINAT INVESTASI RASIONAL PADA GENERASI MILENIAL - Saiful Anuar; Hasanul Bishry; Hendrayani Hendrayani; Iskandar Iskandar; Yogie Rahmat; Herispon Herispon; Rizqi Fakhri; Defi Warman (Komunitas Manajemen Kompetitif, 2026)
This community service activity aims to enhance capital market financial literacy and rational investment interest among the millennial generation through a campus-industry collaborative education model. The program was conducted as a hands-on workshop using the lesson study approach (Plan-Do-See), involving 120 STIE Riau students and Korean Investment & Securities Indonesia (IKISI). Data collection employed pre-test and post-test, participant observation, and in-depth interviews. Results show significant improvement in understanding of capital market concepts (from 32% to 84%), fundamental analysis skills (from 18% to 72%), and use of digital platforms (from 24% to 76%). Academic-practitioner collaboration successfully built self-confidence and rational investment intention. This program recommends the development of tiered training, formation of investment learning communities, and integration of practical materials into the curriculum to sustain youth financial literacy improvement.